Student’s Computational Thinking Process in Solving PISA Questions in Terms of Problem Solving Abilities - M. Gunawan Supiarmo; Heri Sopian Hadi; Tarmuzi Tarmuzi (IKIP Siliwangi, 2022)
Computational thinking is the process of solving problems using logic gradually and systematically needed in the field of mathematics. However, the learning applied by the teacher limits the student's ability to develop computational thinking skills. Teachers are accustomed to providing conventional learning and emphasize student's skills in using formulas. One of the treatments that can be used to stimulate student's computational thinking skills is PISA questions. The purpose of this study was to analyze student's computational thinking processes in solving PISA questions in terms of their problem solving abilities. The research data consisted of student answers, think aloud results, and semi-structured interviews. Data analysis techniques are data reduction, data presentation, and drawing conclusions or verification. The results showed that the computational thinking process of students with low problem solving abilities only reached the decomposition stage because students were able to simplify the problem even though it was incomplete, but they were not able to connect mathematical concepts or materials to build a solution. Meanwhile, students with moderate and high problem solving abilities are limited to the pattern recognition stage because they can simplify problems and develop strategies, but make mistakes in using patterns, and there are incomplete steps. So it can be concluded that the computational thinking process of students with low problem solving abilities only reaches the decomposition stage. The computational thinking process of students with moderate and high problem solving abilities is limited to pattern recognition indicators.